COVID-19 - Mouthwash in dental clinical practice: review - Oliveira , Mirlany Mendes Maciel; Almeida , Arthur Caetano de; Rodrigues, Cristóvão Marcondes de Castros; Sol, Izabella; Meneses-Santos, Daniela (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Severe acute respiratory syndrome (SARS-CoV-2) is a highly infectious respiratory disease. Dental surgeons perform various procedures that generate aerosolization, leading to the dissipation of saliva and drops of blood. The indication during the COVID-19 pandemic in clinical practice is the use of mouthwashes to reduce the viral load of SARS-CoV-2. The present work brings the main rinses indicated in the literature to minimize the viral load of SARS-CoV-2 in clinical practice.